Public Sector Earnings Comparability: Alternative Estimates for the U.S. Postal Service - Belman, Dale; Heywood, John; Voos, Paula (Relations industrielles / Industrial Relations, 2002)
SummaryUsing the postal service as an example, this article highlights the critical role played by a series of “implicit” judgments when estimating the government earnings differential. Regression estimates demonstrate that alternative treatments of location, gender, industry, occupation and union status result in estimates ranging from a double digit advantage for postal workers to no advantage at all. We argue that the standard of comparability, comparing similar workers doing similar work, requires that judgments about samples and controls be made explicit as they largely determine the resulting estimates.